Use of ozone in wound care: scope review - Carneiro Cordeiro Nobre , Vera Patricia; Gehring Junior, Waldemar; Antar Gamba, Mônica; Santos de Souza Oliveira, Lavinia; Taminato, Mônica (Revista Feridas, 2021)
Objective: to identify evidence on the use of ozone in the topical treatment of skin wounds in humans. Method: scope review, carried out in March 2021 in the Cochrane Library, Latin American and Caribbean Literature in Health Sciences, Scientific Electronic Library Online and National Library of Medicine databases with the Health Sciences descriptors in the combinations: Healing, Ozone, Wounds and Injuries. 1352 articles were selected, 129 eligible and analyzed in detail 09. Results: the studies showed that ozone is an advantageous therapy in the healing stimulation of skin wounds due to its various potentialities. Conclusion: there is evidence of the effectiveness of the use of ozone in the treatment of wounds, especially in the form of gas and oils, and further studies are needed in order to parameterize its application and healing indicators.